Situation Report: Romania, 26 November 1986 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Romania Rejects CMEA-Sponsored Reform and Closer Integration / by Anneli Maier Ceausescu Addresses Members of Warsaw Pact Military Council / by Anneli Maier More in the Liviu Bota Case / by Rene de Flers A Reshuffle of Ambassadors Israeli-Palestinian Meeting in Romania / by Anneli Maier The Referendum on Military Cuts: 99.9% Turnout, 100% Approval / by Anneli Maier Electricity and Politics / by Paul Gafton Another Odd Proposal / by Paul Gafton Land Development Endangers the Danube Delta / by Dan Ionescu Rabbi Concerned by Anti-Semitic Poem and Fire a Synagogue / by Crisula Stefanescu